2017
DOI: 10.1007/s12149-017-1151-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acquisition orbit on phase analysis of gated single photon emission computed tomography myocardial perfusion imaging for assessment of left ventricular mechanical dyssynchrony

Abstract: Differences in acquisition orbit had a significant influence on HBW and PSD with Tl-gated SPECT MPI in the inferior wall in patients with major hypoperfusion myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…In addition, reconstructions of projections from a 180‐degree acquisition converge more slowly and to lower activity concentration values than reconstructions of a 360‐degree acquisition. In cardiac imaging, it was shown that a 180‐degree arc was related to inhomogeneities and quantitation errors . This is in line with our results, showing no significant difference in image quality and dosimetric accuracy in images obtained with the HCS protocol compared with images obtained with the uniform projection‐time protocol.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, reconstructions of projections from a 180‐degree acquisition converge more slowly and to lower activity concentration values than reconstructions of a 360‐degree acquisition. In cardiac imaging, it was shown that a 180‐degree arc was related to inhomogeneities and quantitation errors . This is in line with our results, showing no significant difference in image quality and dosimetric accuracy in images obtained with the HCS protocol compared with images obtained with the uniform projection‐time protocol.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the value of phase analysis may vary depending on the software program, even when using the same software (22,23). Additionally, the phase parameter has great variability because the phase histogram is affected by many factors, such as sex, cardiovascular risk factors, including hypertension, diabetes, and kidney disease, and imaging protocol (7,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Acquisition orbits of 180°a nd 360°significantly influenced bandwidth and phase SD in a clinical study. 6 Notably, sex influences phase parameters. 7 When male and female LV end-diastolic volumes were matched in a normal database, entropy was significantly higher in males than in females (26.3% ± 8.0% vs 20.1% ± 5.5%, p = 0.020).…”
mentioning
confidence: 99%